PERSEPSI WISATAWAN TERHADAP PRODUK KULINER DI KAWASAN WISATA ISTANA SIAK SRI INDRAPURA - Wulansari, Sartika; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is to know the tourist's perceptions about the culinary products which sold in the tourism area of Siak Sri Indrapura Palace and the factors which influence these perceptions. This research takes 100 tourists who visited Siak Sri Indrapura Palace as sample. Their perceptions are seen from the perceptions of price, quality and the perceived risk. This research used statistic description analysis techniques and used Likert scale with five alternative answers.The tourist’s perceptions about the culinary products are not so good. It is because there are some factors which make the tourist’s feel bad about the culinary product. For instance, the high price, poor services, etc. The main factors that influence these perceptions are the product appearances, the tourist’s experience, cultures, expectations and motives.Keywords : Perceptions, tourist, culinary product, perceptions of price, quality and the perceived risk.